The Effect of Peer Educator on Adolescent Girl’s Perception About Early Marriage In 21 Tasikmalaya Junior High School - Rahmawati, Jein; Mulyani, Nunung; Suptiani, Laila Putri (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2025)
Early marriage negatively impacts the physical and psychological well-being of children worldwide. Adolescents marry for various reasons influenced by peers, perceptions (cognitive, affective, conative), education, and reproductive health information. Teenagers often depend on peers to understand and foster important relationships. Therefore, peer educator initiatives are carried out to tackle early marriage. This investigation aimed to assess the impact of peer educators on the perceptions of female adolescents regarding early marriage at SMP Negeri 21 Tasikmalaya. This research employed a quantitative methodology, specifically the pre-experimental design characterized by a one-group pre-test post-test framework. The population encompassed all female students enrolled at SMP Negeri 21 Tasikmalaya, amounting to a total of 181 individuals. The purposive sampling technique was employed, yielding a sample size of 40 female students alongside 4 peer educators who had undergone training. The research instrument utilized was a questionnaire addressing adolescent perceptions of early marriage, evaluated through cognitive, affective, and conative aspects. The data collected for the research were analyzed using the Wilcoxon Test. The findings of this study reveal that following educational interventions by peer educators, all female adolescents demonstrate understanding, do not support, and possess positive conative aspects towards early marriage. The results of the statistical analysis indicated a p-value of 0.000. The conclusions drawn from this study indicate that peer educators significantly influence the perceptions of adolescent women regarding early marriage at SMP Negeri 21 Tasikmalaya.